KETOGENIC DIET FOR WEIGHT LOSS AND ITS IMPLICATION ON HEALTH: A LITERATURE STUDY - Rian Diana; Dominikus Raditya Atmaka (Universitas Airlangga, 2020)
The prevalence of obesity has increased signifi cantly and it has become a public health problem globally. Many strategies were done to overcome obesity. One of them is dietary approach. The popular and widely used weight loss diet is the ketogenic diet. This literature review aimed to discuss the mechanism of ketogenic diet in weight lost as well as its long and short term eff ects on health. Ketogenic diet is a very low-carbohydrate and high-fat diet. This diet restricts the carbohydrate intake up to 50 gram per day. The diet eff ective for losing weight in short term (<6 months), after 6 months there was no signifi cant diff erences compared to other wight-loss diet. Study shows ketogenic diet gives both benefi cial and harmful eff ects in short and long term for ketogenic dieters. This diet is not applicable for anyone, thus people with chronic diseases should receive guidance from dietitian or clinician in implementing this diet. Ketogenic dieters are suggested to replace their carbohydrate intake with complex carbohydrate (whole food-not refi ned), reduce animal-based protein, increasing plant-based protein and polyunsaturated fat, water, fermented foods and beverages.